CONSUMPTIVE BEHAVIOR OF BANDUNG TEENAGERS TO ONLINE SHOPPING - Alifa, Salma (Universitas Pendidikan Indonesia, 2023)
Technological developments that occur in the digital era allow people to be able to practice buying and selling indirectly using applications. Teenagers are one part of society that has a tendency to practice buying and selling, especially using the internet. Buying and selling applications offered such as; Shopee, Tokopedia, Lazada. This study uses a qualitative method with a phenomenological approach to adolescent consumptive behavior towards buying and selling practices in online shops. In this study, the data obtained came from interviews conducted with several resource persons who came from among students with a tendency to purchase goods at online shops. The results of this study show that the phenomenon of shopping using an online shop application is caused by the desire to meet needs beyond the primary and secondary needs carried out by adolescents, on the one hand this behavior is beneficial for creative economic actors contained in online applications but on the other hand this phenomenon shows a consumptive attitude that shown by most teenagers.